People from Countries West and North of Babylonia in Babylon during the Reign of Nebuchadnezzar - Ṣādōq, Ran (Hebrew bible and ancient Israel, 2018)
Six uneven categories of people from the Levant, Egypt, Anatolia and the Jazira are recorded in the capital of Babylon during Nebuchadnezzar II's reign. Most of them are recipients of rations according to the royal archive N1. The most numerous category consists of the prisoners of Nebuchadnezzar II's campaigns to the west and northwest.